2008
DOI: 10.1016/j.juro.2008.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention and Post-Void Residual Urine in Men: Separating Truth From Tradition

Abstract: Clinicians are adopting less invasive approaches (eg pharmacology or catheterization) to treating patients who present with the symptoms, sign, and condition of urinary retention. Faced with an abundance of new data on acute urinary retention, urologists need to reach a consensus about the risks of urinary retention; this may promote movement toward patient centered prevention strategies with tailored treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 54 publications
2
81
1
4
Order By: Relevance
“…There are no clear defining characteristics of urinary retention, such as a specific volume of urine or elapsed time postoperatively without micturition; however, in accordance with the consensus view in the contemporary literature, urinary retention would be described as an inability to initiate micturition with a bladder volume exceeding 500 mL. 6 Urinary retention can be complete or partial, acute or chronic, painful or silent, obstructive or non-obstructive. ''Overflow'' incontinence secondary to excess intravesical pressure can occur.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…There are no clear defining characteristics of urinary retention, such as a specific volume of urine or elapsed time postoperatively without micturition; however, in accordance with the consensus view in the contemporary literature, urinary retention would be described as an inability to initiate micturition with a bladder volume exceeding 500 mL. 6 Urinary retention can be complete or partial, acute or chronic, painful or silent, obstructive or non-obstructive. ''Overflow'' incontinence secondary to excess intravesical pressure can occur.…”
Section: Résumémentioning
confidence: 99%
“…The long-term consequences of postoperative urinary retention (POUR) are not always immediately apparent in the perioperative period, although increased hospital length of stay and prolonged detrusor dysfunction have been documented. 1,6 Neuraxial local anesthetics block the afferent and efferent limbs of the micturition reflex resulting in detrusor dysfunction and the inability to sense a full bladder, thus impairing micturition. Neuraxial opioids enhance this effect by decreasing the sensation of bladder fullness, thus increasing bladder capacity and weakening detrusor contraction through their actions at the spinal level and in the pontine micturition centre.…”
Section: Résumémentioning
confidence: 99%
“…Although many etiologic factors have been identified (which are classified under three main categories: obstructive, neurogenic and myogenic), BPH is thought to be the most prevalent. [2] The exact causative mechanism of AUR remains under debate. [8] Several community-and population-based studies have clearly demonstrated that the incidence of AUR increases with age, particularly in men over age 70.…”
Section: Discussionmentioning
confidence: 99%
“…[1] AUR may develop into urinary infection, permanent bladder dysfunction and even renal insufficiency. [2][3][4] The most common cause of obstructive AUR is benign prostatic hyperplasia (BPH). [3] Because of the age-dependent nature of BPH, the risk of AUR increases with age (10-30% with every 5-year age increase).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to determine the usefulness of urine culture as screening methods and the correlation between symptomatic UTI and stricture recurrence. Ultrasound PVR measurement is noninvasive technique that provide objective measurement of bladder emptying [24]. One may predict that high PVR volume would predict stricture.…”
Section: Urethral Stricturementioning
confidence: 99%